Classification of Emg Signals Using Convolution Neural Network - Kaan BAKIRCIOĞLU; Nalan ÖZKURT (International Journal of Applied Methods in Electronics and Computers, 2020)
An electrical signal is produced by the contraction of the muscles; this electrical signal contains information about the muscles, the recording of these signals called electromyography (EMG). This information is often used in studies such as prosthetic arm, muscle damage detection, and motion detection. Classifiers such as artificial neural networks, support vector machines are generally used for the classification of EMG signals. Despite successful results with such methods the extraction of the features to be given to the classifiers and the selection of the features affect the classification success. In this study, it is aimed to increase the success of the classification of the daily used hand movements using the Convolutional neural networks (CNN). The advantage of the deep learning techniques like CNN is that the relationships in big data are learned by the network. Firstly, the received EMG signals for forearms are windowed to increase the number of data and focus on the contraction points. Then, to compare the success rate, raw signals, Fourier transform of the signal, the root means square, and the Empirical mode decomposition (EMD) is applied to the signal and intrinsic mode functions are obtained. These signals are given to four different CNN. Afterward, to find the most efficient parameters, the results were obtained by splitting data set into three as 70% training set, 15% validation set, and 15% test set. 5 cross-validations have been applied to assess the system’s performance. The best results are obtained from the CNN, which receive the EMD applied signal as input. The result obtained with the cross-validation is 95.90% and the result obtained with the other separation method is 93.70%. When the results were examined, it was seen that CNN is a promising classifier even the raw signal is applied to the classifier. Also, it has been observed that EMD method creates better accuracy of classification. This is an open access article under the CC BY-SA 4.0 license. (https://creativecommons.org/licenses/by-sa/4.0/)